Expanding Clinical Pharmacy Services: A Systematic Review of Pharmacist and Assistant Pharmacist Contributions to Patient Care in Saudi Arabia - Abdallah Saud Radi Aldhafeer, Nasser Mansour Hashr Almutairi, Ali Hassan Mohsan Almutairi, Mohammed Hussain Abdullah Almutairi, Sattam Nawaf Owish Alzabni, Yousef Eid Noban Almotiri, Ajlan Muttalib Al Shammari, Bassam Saeed Hammad Albathali (Journal of International Crisis and Risk Communication Research, 2024)
Saudi Arabia has been undergoing a healthcare transformation as part of the Vision 2030 strategic plan, which aims to improve the quality, accessibility, and efficiency of healthcare services. Pharmacists and assistant pharmacists play a crucial role in delivering patient care and ensuring medication safety and effectiveness. This systematic review aimed to synthesize the evidence on the contributions of pharmacists and assistant pharmacists to expanding clinical pharmacy services in Saudi Arabia. A comprehensive search of PubMed, CINAHL, Scopus, and Google Scholar databases was conducted for studies published between 2012 and 2024. A total of 30 studies met the inclusion criteria and were analyzed using a narrative synthesis approach. The findings revealed that pharmacists and assistant pharmacists are involved in various clinical pharmacy services, such as medication therapy management, patient education and counseling, immunization, and specialty pharmacy services. However, several barriers were identified, including the lack of recognition and collaboration from other healthcare professionals, limited resources and infrastructure, and inadequate education and training. The implications for practice and policy included the need for developing a national framework for clinical pharmacy practice, investing in pharmacy workforce development and technology, and promoting interprofessional collaboration and patient-centered care. The review highlights the importance of leveraging the expertise and skills of pharmacists and assistant pharmacists in achieving the healthcare goals of Saudi Vision 2030.